2004
DOI: 10.2337/diacare.27.5.1066
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes, Depression, and Quality of Life

Abstract: OBJECTIVE -The aim of the study was to assess the prevalence of diabetes and depression and their associations with quality of life using a representative population sample.RESEARCH DESIGN AND METHODS -The study consisted of a representative population sample of individuals aged Ն15 years living in South Australia comprising 3,010 personal interviews conducted by trained health interviewers. The prevalence of depression in those suffering doctor-diagnosed diabetes and comparative effects of diabetic status and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
380
3
33

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 560 publications
(448 citation statements)
references
References 25 publications
32
380
3
33
Order By: Relevance
“…High rates of depression have also been observed in Australia in both individuals with type 1 and type 2 diabetes (Hislop et al, 2008, Goldney et al, 2004, Jordan (AlAmer et al, 2011), Pakistan and Qatar (Bener et al, 2011).…”
Section: International Variations In Prevalence Of Depression In Diabmentioning
confidence: 96%
“…High rates of depression have also been observed in Australia in both individuals with type 1 and type 2 diabetes (Hislop et al, 2008, Goldney et al, 2004, Jordan (AlAmer et al, 2011), Pakistan and Qatar (Bener et al, 2011).…”
Section: International Variations In Prevalence Of Depression In Diabmentioning
confidence: 96%
“…Cross-sectional studies consistently show an association between asthma and depression (1,(8)(9)(10)(11)(12); however, temporality of the association has not been established (13). Mental health problems can impact awareness of and adherence to the treatment of asthma; thus, depression is associated with poor asthma control, which can lead to an increase in asthma exacerbations (14)(15)(16).…”
Section: At a Glance Commentarymentioning
confidence: 99%
“…Recent research has suggested that subsyndromal depression, defined as the presence of depressive symptoms that fall short of full diagnostic criteria for major depression or dysthymia, has a profound influence on the affected patients' quality of life and may be a part of a continuum of depressive disorders [18,19]. Data from the general population indicate that spontaneous remission rates for this type of mood disturbance are low [20].…”
Section: Introductionmentioning
confidence: 99%